WEEDS CONTROL WITH HERBICIDE DOSAGE AND FREQUENCY OF PGPR TOWARD GROWTH AND YIELD OF PADDY CROPS - Avino Sudhana; Siwi Hardiastuti; Oktavia Sarhesti Padmini (Jurnal Agrivet, 2018)
The first aim of this research was to determine dose of herbicide and frequency of Plant Growth Promoting Rhizobacteria application that efficient to control weeds toward growth and yield of paddy crops. fertilization on the growth and brix value of sweet sorghum cultivated on marginal land. The factorial experiment was arranged in randomized completely block design, with three treatments. The first factor was dose of herbicide with three levels: H0 = without herbicide application, H1 = 1,25 L/ha, and H2 = 1,5 L/ha. The second factor was frequency of PGPR applications with three levels: P0 = without PGPR application, P1 = one time application, and P2 = two times application, each treatment was repeated three times.. Analysis of variance was used for data analysis, and than followed with Duncan Multiple Range Test (DMRT) if there was a significant different. The result showed that the herbicide application with cyhalofop-butyl and penoxsulam active ingredient doses of 1,25 L/ha and 1,5 L/ha was significantly increased weeds control efficiency per species above 90% (92-99%), shoot root ratio (34-40%), and dry weight of grain per hectare (7-8 tons/ha) than without herbicide application. Frequency of PGPR applications has no significantly effect on all parameters.Keywords: weeds, herbicide, PGPR, rice